2015
DOI: 10.1039/c4ra09781e
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt phthalocyanine tetracarboxylic acid modified reduced graphene oxide: a sensitive matrix for the electrocatalytic detection of peroxynitrite and hydrogen peroxide

Abstract: The electrocatalytic properties of cobalt phthalocyanine modified reduced graphene oxide for peroxynitrite and hydrogen peroxide are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 71 publications
4
35
0
Order By: Relevance
“…Recent studies have suggested that CoPc aggregation occurs when CoPc is adsorbed to carbon surfaces at high loadings 39,51,52 and that this aggregation limits the number of exposed active sites and, therefore, the measured per-CoPc TOFs 39 . To explore whether aggregation influences the results of our mechanistic studies, we explored the loading dependence on CO 2 RR activity by CoPc both physisorbed onto EPG and within the P4VP films over four orders of magnitude of loading between 2.19 × 10 −11 mol cm −2 and 2.19 × 10 −7 mol cm −2 (results are summarized in Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that CoPc aggregation occurs when CoPc is adsorbed to carbon surfaces at high loadings 39,51,52 and that this aggregation limits the number of exposed active sites and, therefore, the measured per-CoPc TOFs 39 . To explore whether aggregation influences the results of our mechanistic studies, we explored the loading dependence on CO 2 RR activity by CoPc both physisorbed onto EPG and within the P4VP films over four orders of magnitude of loading between 2.19 × 10 −11 mol cm −2 and 2.19 × 10 −7 mol cm −2 (results are summarized in Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, transition metal porphyrins and similar molecular complexes are known to self‐assemble on coinage metal supports . Several studies have been devoted towards understanding the molecule‐support interaction of transition metal–porphyrins or pthalocyanines on supports such as gold, silver, copper, platinum or even non‐metal surfaces such as graphene,, graphene oxide,, and carbon nanotubes ,,. Depending on the strength/nature of the interaction between metal surface and organometallic homogeneous catalyst, the charge, spin, or magnetism of the adsorbed molecular catalyst can be modified which in turn may influence its catalytic properties …”
Section: Introductionmentioning
confidence: 99%
“…Studies of the biochemical roles of the PON precursors, nitric oxide and superoxide anion, have been performed using electrochemical detection methods for real-time, label-free and direct measurement of these reactive species [1719]. There are some reports of the direct detection of PON by electroanalytical techniques reported in the literature [1428]. Amatore and co-workers studied the electrochemical oxidation of PON by steady-state and transient voltammetry with platinized carbon microelectrodes [1518].…”
Section: Introductionmentioning
confidence: 99%
“…Chemically-modified platinum microelectrodes coated with manganese tetraaminophthalocyanine films were utilized for PON detection in alkaline solution (pH 10.2) where it is more stable [21]. More recently, it was shown that improved catalytic PON activity could be achieved by depositing nanostructured metalloporphyrin or metallophtalocyanine films onto glassy carbon or carbon fiber electrodes [25-28]. …”
Section: Introductionmentioning
confidence: 99%